PENGARUH BUDAYA PERUSAHAAN TERHADAP KETERIKATAN KARYAWAN DI PT DENTSU AEGIS NETWORK INDONESIA - Surahmad Surahmad; Ratu Nadya W; Uljanatunnisa Uljanatunnisa (Dialektika, 2017)
The increasing number of multinational companies in Indonesia, and one of them is a company engaged in the media agency, namely PT Dentsu Aegis Network Indonesia. Because it is a multinational company of course affects the entire management of PT Dentsu Aegis Network Indonesia management, most of the management of PT Dentsu Aegis Network Indonesia are people from different countries and cultural backgrounds. In addition, it is interesting that PT DAN was previously two different companies namely PT Dentsu and Aegis. But in 2014 has been merged and in 2016 the management of PT DAN has done a new office relocation to support their long-term plan. So that once between PT Dentsu and PT Aegis apart now has been in one roof. Then can be seen from the background will form the culture of a diverse company. The application of corporate culture in the internal environment of employees is the first step to provide convenience for adaptation and interaction process, in an effort to create a conducive working atmosphere amid increasing market competition. It can be said that corporate culture is the basic foundation of employee loyalty creation to the company. Take samples of 86 employees of corporation with correlational quantitative data collection technique that is research by way of processing and presentation of data by using statistical method that is regression analysis with purpose to determine influence of company culture to employee's attachment to PT Dentsu Aegis Network Indonesia so as enable researcher to conclude objective condition. Based on table t test examination obtained value of tcount (9.712)> table (1,291) so Ho is rejected and H1 is accepted means there is corporate culture to employee engagement.